O THE TRANSFORMATIVE ROLE OF ARTIFICIAL INTELLIGENCE IN SECURITY - Leite, Erik Henrique; Ribeiro, Douglas Francisco (Revista Interface Tecnológica, 2023)
The revolution brought by AI in the way we store sensitive data, such as banking information, photos, and emails, as well as in our interaction with machines. Recognizing that every evolution has its positive and negative aspects, we will comprehensively address the implications of this transformation, providing clear information on how to stay safe while harnessing the benefits of this technology.Furthermore, we will dedicate a section of the article to explore the consequences of AI and the growing dependency on data, highlighting the challenges and ethical considerations associated with its use in the context of security. We hope that this project will provide a deeper understanding of the effects of AI in the security landscape, offering important guidelines to effectively deal with the implications and challenges arising from this technological evolution.
Keywords: data dependency; AI (Artificial Intelligence); Data storage